Strategies of coping with stress and the sport results of alpine skiers and tennis players - Knittel Michał; Guszkowska Monika (Sciendo, 2016)
Study aim: The aim of the study was to determine the relationship between strategies of coping with stress caused by participating in sport competitions and the results of those competitions, as well as to differentiate the applied coping strategies according to the practiced sport discipline (tennis and alpine skiing).